Psychosocial outcomes in children with and without non-syndromic craniosynostosis: findings from two studies - Cloonan, Yona K (2012)
OBJECTIVE: To evaluate the hypothesis that children with craniosynostosis and their parents have differences in psychosocial outcomes, as compared with an unaffected control group. DESIGN: Two studies were conducted, both which followed children born with and without craniosynostosis. Study 1 ascertained affected children from clinics and Study 2 ascertained affected children from a population-based study of birth defects. PARTICIPANTS: Study 1 included 22 children with single-suture craniosynostosis and 18 controls, ages 4–5 years. Study 2 included 24 children with non-syndromic craniosynostosis and 124 unaffected controls, ages 5–9 years. MAIN OUTCOME MEASURES: Outcome measures included the Child Behavior Checklist (CBCL), Social Competence Scale (SCS), Pediatric Quality of Life Inventory (PedsQL(™)), and Parenting Stress Index (PSI). RESULTS: We observed lower scores on measures of health-related quality of life in cases versus controls, with adjusted effect sizes ranging from −0.72 to −0.44 (p<0.05) on summary measures. Small but statistically non-significant increases in behavioral problems were observed in cases versus controls, with no apparent differences in social competence or parenting stress. CONCLUSIONS: Results provide preliminary evidence suggesting that children with non-syndromic craniosynostosis may have elevated risk for psychosocial difficulties, particularly health-related quality of life. Continued follow-up through pre-adolescence and adolescence is warranted.